SOLUTION OF THE QUESTION OF CSR AND MARKETING CHALLENGES - Mária Holienčinová; Ľudmila Nagyová; Ingrida Sedliaková (Polityki Europejskie, Finanse i Marketing)
The topic of sustainability has taken center stage around the world and has driven the attention and focus of a growing number of powerful voices and interests around the world. Constantly increasing competitive and social tension forces companies to find new approaches in business behaviour. Increasing needs force companies to support these demands sustainably. Initiatives of corporate social responsibility (CSR) should be incorporated into strategy in every business entity. The purpose of this paper is to determine the importance of CSR and new marketing approaches through sustainable marketing in business activities. In order to fulfill defined objectives of the paper were collected and used primary and secondary sources of information, as well as the method of interview using a questionnaire (total number of respondents was 120 agrifood entities).